Coordinated Development of Muscles and Tendon-Like Structures: Early Interactions in the Drosophila Leg - Soler, Cedric; Laddada, Lilia; Jagla, Krzysztof (Frontiers in Physiology, 2016)
The formation of the musculoskeletal system is a remarkable example of tissue assembly. In both vertebrates and invertebrates, precise connectivity between muscles and skeleton (or exoskeleton) via tendons or equivalent structures is fundamental for movement and stability of the body. The molecular and cellular processes underpinning muscle formation are well established and significant advances have been made in understanding tendon development. However, the mechanisms contributing to proper connection between these two tissues have received less attention. Observations of coordinated development of tendons and muscles suggest these tissues may interact during the different steps in their development. There is growing evidence that, depending on animal model and muscle type, these interactions can take place from progenitor induction to the final step of the formation of the musculoskeletal system. Here we briefly review and compare the mechanisms behind muscle and tendon interaction throughout the development of vertebrates and Drosophila before going on to discuss our recent findings on the coordinated development of muscles and tendon-like structures in Drosophila leg. By altering apodeme formation (the functional Drosophila equivalent of tendons in vertebrates) during the early steps of leg development, we affect the spatial localisation of subsequent myoblasts. These findings provide the first evidence of the developmental impact of early interactions between muscle and tendon-like precursors, and confirm the appendicular Drosophila muscle system as a valuable model for studying these processes.